Efficacy of E-Recruitment from a Job Seeker’s Perspective - Rumani Shah, Akshat Sharma (International Journal of Advanced Science and Technology, 2020)
Today the landscape of every sector, every industry and every practice in business has changed drastically for the emergence of Internet and digitization in every sphere. In business, the recruitment procedure for an employee to join a firm has been totally changed and altered by the Internet, and thus the customary and sluggish procedure of recruitment is changed for the new procedure that is known as ’E-Recruitment’. Otherwise called "online recruitment", it is the utilization of innovation or the tech-network instruments to help the recruitment procedure. Irrespective of their shapes and sizes, associations are utilizing Internet as a wellspring of recruitment. The triggers of social media, the ease of communication and connecting different people worldwide, have been brought to these organization’s attention, who are increasingly using these triggers to attract and retain their employees. Social media channels such as Facebook, Twitter, LinkedIn, are the developing and more efficient mode of connecting everywhere throughout the world, whereas systematized and effective recruitment is one of the most significant needs of organizations. Talent hunting and acquisition through social media has become a regular affair. E-recruitment is another wonder that prompted the presence of another market where there is an extraordinary degree of association among employer and employees. Today, every organization inspired by recruitment and the ever-developing social media sway in the employment vertical. This paper will emphasize on the efficacy of the technology of having E-Recruitment platforms and will also dig deeper into the side of the job seekers to evaluate the satisfaction levels that these accessible and modern instruments have brought upon them.